1990
DOI: 10.1042/bj2680281
|View full text |Cite
|
Sign up to set email alerts
|

4-O-(1-carboxyethyl)-l-rhamnose, a second unique acidic sugar found in an extracellular polysaccharide from Butyrivibrio fibrisolvens strain 49

Abstract: Butyrivibrio fibrisolvens strain 49 excretes a polysaccharide that contains D-glucose, D-galactose, 4-O-(1-carboxyethyl)-D-galactose, and an acidic component of previously unknown structure. We report here the identity of the unknown as 4-O-(1-carboxyethyl)-L-rhamnose. The structure of this previously unknown compound was deduced from (1) comprehensive electron-impact and chemical-ionization mass-spectroscopic studies of differentially labelled derivatives prepared from the unknown, (2) 13C-n.m.r. and 1H-n.m.r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Presumably, the EP aids in this associ-ation and possibly hinders diffusion of the diverse extracellular enzymes such as xylanases (9), proteases (2), or esterases (10) made by B. fibrisolvens. The EP may also serve in a protective role since the presence of unusual sugars might make the EP more resistant to the action of glycanases (19,24). Regardless of the natural roles, the EPs of some B. fibrisolvens strains may have potential commercial applications on the basis of their rheological properties, as shown in this study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Presumably, the EP aids in this associ-ation and possibly hinders diffusion of the diverse extracellular enzymes such as xylanases (9), proteases (2), or esterases (10) made by B. fibrisolvens. The EP may also serve in a protective role since the presence of unusual sugars might make the EP more resistant to the action of glycanases (19,24). Regardless of the natural roles, the EPs of some B. fibrisolvens strains may have potential commercial applications on the basis of their rheological properties, as shown in this study.…”
Section: Discussionmentioning
confidence: 76%
“…EPs from several strains have been characterized on the basis of sugar composition (20). The compositional analysis of EPs produced by 37 strains of B. fibrisolvens showed that unusual sugars such as L-altrose (19,21), 4-O-(1-carboxyethyl)-D-galactose (23), and 4-O-(1-carboxyethyl)-L-rhamnose (24) are common constituents of the EPs. However, the rheological and functional properties of these EPs have not been studied.…”
mentioning
confidence: 99%
“…An interesting observation was the presence of 4-O-(1-carboxyethyl)-rhamnose in the EPS of strain 20-63. This unusual acidic sugar was previously found only in the EPS of specific strains of another anaerobic gastrointestinal bacterium, Butyrivibriofibrisolvens (20,33). We have speculated that unusual sugars in the EPS of gastrointestinal bacteria may serve to protect the bacteria from glycanases and/or glycosidases found in the digestive tracts of animals (31).…”
Section: Discussionmentioning
confidence: 80%